THE EFFECTIVENESS OF COMICS LEARNING MEDIA TO IMPROVE THE TOLERANCE ATTITUDE OF JUNIOR HIGH SCHOOL LEVEL STUDENTS - Anggraeni Sugiarto, Apprillia; Kurniawan , Dandi; Ridwan, Muhammad; Sudarwati, Ninik (Jurnal PTK dan Pendidikan, 2024)
The motto "Bhinneka Tunggal Ika" is the basis for diversity in Indonesia. However, the level of tolerance is a concern, especially regarding the disapproval of exclusive groups. This research emphasizes the importance of the value of tolerance, particularly among the nation's younger generation. Education is considered a platform for building tolerance by including subject matter that explores understanding of cultural, religious, and ethnic diversity. This research focuses on the use of comics as learning media, which can capture students' attention through a combination of pictures and stories, helping them understand the values of tolerance more deeply. This Classroom Action Research (PTK) aims to measure the effectiveness of using comics to increase understanding of the value of tolerance among students of class VIII-D at SMPN 3 Jombang. The results show that the percentage obtained by students in the pre-cycle only up to 6%, then in cycle I a percentage of 59% was achieved using an average of 76.25. In cycle II, there was a significant increase, reaching 94% with an average score of 84.66. In conclusion, comic learning media is effective in the learning process because it can enhance students' knowledge and understanding of the importance of tolerance.